Carbon sequestration, tree biomass growth and rubber yield of PB 260 clone of rubber tree (Hevea brasiliensis) in North Sumatra - Sone K; Gyokusen K; Hosaka T; Takase M; Watanabe N (Journal of Rubber Research, 2014)
It is desirable to supply the rising demand for industrial crop materials without increasing the amount of land cultivated for crops, if possible. Quantitative information about biomass growth and carbon sequestration by crops is fundamental knowledge that can be used to improve crop yield per unit of cultivation area. In the present study, measured trunk diameter, tree height and biomass of a PB 260 clone of the Para rubber tree, Hevea brasiliensis (Willd.) Muell. Arg. The natural rubber from this tree is used mainly to make tyres and is one of the most important industrial crop materials. Also measured the soil carbon in stands that had been planted from two to 20 years earlier in northern Sumatra, Indonesia. The biomass of each tree was estimated from the measurement of the trunk diameter and these data were combined with the rubber yield data in order to estimate the amount of carbon sequestered annually by the estate as a whole.The tree biomass growth and rubber yield rates peaked at eight and ten years after planting, respectively. After that point, the tree growth rate declined more rapidly than the rubber yield rate. As a result, the percentage of the trees overall biomass composed by rubber consistently increased from 5;in a three year old tree to 40;in a 20 year old tree. The estimated annual carbon sequestered as tree biomass and as rubber were 4.2 tC ha-1 year-1 and 1.9 tC ha-1 year-1, respectively.
Source Year: 2014
Keywords: Allometry; Biomass; Carbon sequestration; PB 260 clone; Rubber yield; Trunk diameter